KEKETATAN ANGGARAN DAN KELELAHAN EMOSIONAL: AMBIGUITAS PERAN SEBAGAI MEDIATOR DAN KEPERCAYAAN SEBAGAI MODERATOR - Luthfihani, Chindy Anggraeni; SeTin, SeTin (Jurnal Riset Akuntansi, 2025)
The COVID-19 pandemic has significantly impacted the hospitality sector, including decreased revenue and low occupancy rates, forcing hotel management to implement budget tightness. This study aims to analyze the effect of changes in budget tightness on emotional exhaustion through role ambiguity as a mediator, with trust in senior management as a moderator. This study uses quantitative methods with questionnaires distributed to star hotel managers in West Java. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The results showed that budget tightness has a positive relationship with role ambiguity, which in turn increases emotional exhaustion. In addition, trust in senior management strengthens the relationship between budget tightness and role ambiguity. These findings emphasize the importance of role clarity and management strategies to reduce emotional exhaustion amid budget pressures. Practical implications of this study include developing policies that support employee well-being as well as improving communication and training to help employees cope with role ambiguity. This study contributes to the literature by expanding the understanding of the relationship between budget tightness, role ambiguity, emotional exhaustion, and trust in senior management in the post-COVID-19 pandemic hospitality industry. Keywords: budget tightness, role ambiguity, emotional exhaustion, trust